2014
DOI: 10.1039/c4cp01259c
|View full text |Cite
|
Sign up to set email alerts
|

Operating mechanisms of electrolytes in magnesium ion batteries: chemical equilibrium, magnesium deposition, and electrolyte oxidation

Abstract: Since the early nineties there have been a number of reports on the experimental development of Mg electrolytes based on organo/amide-magnesium chlorides and their transmetalations. However, there are no theoretical papers describing the underlying operating mechanisms of Mg electrolytes, and there is no clear understanding of these mechanisms. We have therefore attempted to clarify the operating mechanisms of Mg electrolytes by studying the characteristics of Mg complexes, solvation, chemical equilibrium, Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…7,32 Since the ion configurations and their solvation structures at the interface are predetermined by those in the bulk solution, in most of the studies the electrochemical stability windows are derived from the properties of electrolytes computed for the bulk. 6,31,33,34 However, in the conventional picture of multivalent ion deposition, 35 the details of the transition from a fully charged and highly coordinated form of a metal cation to its partially discharged and lower coordinated form remain largely unclear. The vicinity of the electrified anode surface may significantly impact the ion coordination and the solvent dynamics 36 and thus the relative time scales of the solvent reorganization and intrinsic electron transfer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,32 Since the ion configurations and their solvation structures at the interface are predetermined by those in the bulk solution, in most of the studies the electrochemical stability windows are derived from the properties of electrolytes computed for the bulk. 6,31,33,34 However, in the conventional picture of multivalent ion deposition, 35 the details of the transition from a fully charged and highly coordinated form of a metal cation to its partially discharged and lower coordinated form remain largely unclear. The vicinity of the electrified anode surface may significantly impact the ion coordination and the solvent dynamics 36 and thus the relative time scales of the solvent reorganization and intrinsic electron transfer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The concentration-dependent instability of the Mg(TFSI) 2 salt at Mg metal potentials was assigned to a drastic decrease of dissociation energy of the C−S bond in the cation-reduced (MgTFSI) 0 complex leading to its decomposition into neutral [Mg + −CF 3 SO 2 NSO 2 − ] 0 and CF 3 fragments. 31 However, the relationship between the solute concentration and the electrochemical stability of anions is far from being fully understood and is still debated 4,6,28,30,53 since the proposed mechanism does not exclude other processes involving solvent impurities or predicted cleavage of the (TFSI) − ion on the Mg surface. 6,54 Given the complexity and richness of the electrochemistry of the Mg(TFSI) 2 /G2 electrolyte, we present an in-depth ab initio study to elucidate the connection between relevant solvation structures of complexes formed in the bulk solution and their electrochemical stability in the vicinity of the Mg metal anode and formulate a set of general guidelines for selection or design of stable electrolytes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore shifts the equilibrium toward the formation of [MgCl] + , arguably the electro-active carrier for Mg 2+ deposition (Kim et al, 2014; Liu et al, 2014) providing an effective way to tune the performance of the Mg-NaCrO 2 battery by controlling the ratio between Mg-APC and Na(CB 11 H 12 ) in dual-salt electrolyte. Using non-carbon-coated NaCrO 2 cathode, we found that the highest discharge capacity was achieved when using a 3:7 volumetric mixture of 0.4 M Mg-APC and 0.5 M Na(CB 11 H 12 ), which was the dual salt electrolyte used in the following tests.…”
Section: Resultsmentioning
confidence: 99%
“…Mg 0.07 V 2 O 5 is a promising cathode in Mg batteries. [49,50] We sought to determine the properties of this material in the presence of the best performing ionic liquids as described above. Figure 6A shows cyclic voltammetry data within the voltage stability range for 1M1PPi/acetonitrile.…”
Section: Performance With High-voltage Cathodesmentioning
confidence: 99%